Interlingual Homonyms of Polysemic Origin in Related Languages - Marta Lackova; Eva Lelakova (Communications - Scientific letters of the University of Zilina, 2014)
The article deals with lexical units of homonymic character functioning on the inter-linguistic level in Slavic languages. The emphasis is put on interlingual homonyms with the origin in the semantic relation of polysemy. In order to provide a theoretical background, the differences between homonymy and polysemy are highlighted. Moreover, homonyms are defined and classified taking into account their etymology. The principal part focuses on the relation: a polysemic homonym in one language - a monosemic homonym in the other one and vice versa.